Nuevas combinaciones, una epitipificación y una corrección nomenclatural en Thelocephala (Cactoideae: Notocacteae): género endémico de Chile - SALDIVIA PÉREZ, PATRICIO; FAÚNDEZ YANCAS, LUIS (Gayana Botánica, 2011)
Within the revision works of the Thelocephala genus it is necessary to carry out new combinations for generic entities recently described under the broad concept of Eriosyce. Additionally, it has been made a correction for one of the binomies used by F. Ritter in 1980 and an epitype is designated for one of the recent taxa.